Methods and techniquesAlternative treatment approach to late graft occlusion of femoropopliteal artery: subintimal tracking and stenting to occluded native artery via transpedal pathway - Tatli, Ersan; Vatan, Mehmet; Aksoy, Murat; Can, Yusuf (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
There are various options for the treatment of occluded femoropopliteal (fem-pop) bypass graft. Although surgical revision is the gold standard, it is also associated with higher rates of complications such as nerve injury, wound and graft infection, and bleeding. In this case report we present the case of fem-pop in graft occlusion in which percutaneous angioplasty and stenting was performed to the occluded native fem-pop artery via transpedal pathway. With this case we tried to emphasise that percutaneous intervention to the native artery could be an alternative to surgical treatment.